Factors Associated with Hypertension Control Behavior in the Pre-Elderly Group in Padangsidimpuan City - Raysyah Rahmadhani Hasibuan; Kintoko Rochadi; Fazidah Aguslina Siregar (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Indonesia is currently facing a double burden of disease, namely communicable diseases and non-communicable diseases, where behavior is one of the causes of changes in the pattern of these diseases. One of the non-communicable diseases which is the main cause of premature death in the world, namely hypertension is a silent killer with the highest prevalence rate in Indonesia. Untreated hypertension can cause complications. The elderly population is the most vulnerable population suffering from hypertension. One of the areas in North Sumatra with an ever-increasing number of cases of hypertension is Padangsidimpuan City. This study aims to analyze factors related to hypertension control behavior in the pre-elderly group in Padangsidimpuan City. This type of research is quantitative analytic with cross sectional design. The total population in this study was 3104 with a total sample of 237 obtained using cluster sampling and proportional random sampling. The instrument in this study used a questionnaire. The data obtained were analyzed by univariate, bivariate, and multivariate using multiple logistic regression tests. The results showed that there was a relationship between intention (p=0.002), knowledge (p=<0.001), attitude (p=<0.001), affordability of information (p=<0.001), availability of facilities and infrastructure (p=0.020), and support social status (p=0.002) with hypertension control behavior. Multivariate analysis shows that the attitude variable is the variable most related to the behavior of the elderly in controlling hypertension with a Prevalence Ratio (RP) value of 4.869. The pre-elderly group is expected to be more active in adopting a healthy lifestyle, and an active role from the family and health workers is needed in providing support to hypertension sufferers to implement hypertension control behavior and avoid complications. Keywords: Behavior, Hypertension Control, Pre-Elderly